Lewy body disease or diseases with Lewy bodies? - Menšíková, Kateřina; Matěj, Radoslav; Colosimo, Carlo; Rosales, Raymond; Tučková, Lucie; Ehrmann, Jiří; Hraboš, Dominik; Kolaříková, Kristýna; Vodička, Radek; Vrtěl, Radek; Procházka, Martin; Nevrlý, Martin; et al. (NPJ Parkinson's disease, 2022)
The current nosological concept of α-synucleinopathies characterized by the presence of Lewy bodies (LBs) includes Parkinson's disease (PD), Parkinson's disease dementia (PDD), and dementia with Lewy bodies (DLB), for which the term "Lewy body disease" (LBD) has recently been proposed due to their considerable clinical and pathological overlap. However, even this term does not seem to describe the true nature of this group of diseases. The subsequent discoveries of α-synuclein (αSyn), SNCA gene, and the introduction of new immunohistochemical methods have started intensive research into the molecular-biological aspects of these diseases. In light of today's knowledge, the role of LBs in the pathogenesis and classification of these nosological entities remains somewhat uncertain. An increasingly more important role is attributed to other factors as the presence of various LBs precursors, post-translational αSyn modifications, various αSyn strains, the deposition of other pathological proteins (particularly β-amyloid), and the discovery of selective vulnerability of specific cells due to anatomical configuration or synaptic dysfunction. Resulting genetic inputs can undoubtedly be considered as the main essence of these factors. Molecular-genetic data indicate that not only in PD but also in DLB, a unique genetic architecture can be ascertained, predisposing to the development of specific disease phenotypes. The presence of LBs thus remains only a kind of link between these disorders, and the term "diseases with Lewy bodies" therefore results somewhat more accurate.